2022
DOI: 10.1088/1755-1315/967/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic abundance in sea cucumber at seagrass ecosystem of Bintan Island and surrounding area, Indonesia

Abstract: The increasing use of plastic in various aspects of life impacts the increase in plastic waste in the environment. The plastics are degraded into the smallest fragments to a size of <5 mm called microplastics. Further, microplastics will accumulate in the water, marine biota, and sediment. Sea cucumbers are deposited feeder and found in the seagrass ecosystem. This study aims to examine the abundance of microplastics in sea cucumbers, which are scattered in seagrass ecosystems in the waters of Bintan Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Fibers were the dominant microplastic type, up to 99% of all samples in this study. Similar results were reported by various researchers in different sea cucumber species and also different sediment samples (Husin et al, 2021;Idris et al, 2022;Mohsen et al, 2019). Fragment was the dominant only in the Holothoria floridana in Placencia Lagoon, Belize, Caribbean (Coc et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fibers were the dominant microplastic type, up to 99% of all samples in this study. Similar results were reported by various researchers in different sea cucumber species and also different sediment samples (Husin et al, 2021;Idris et al, 2022;Mohsen et al, 2019). Fragment was the dominant only in the Holothoria floridana in Placencia Lagoon, Belize, Caribbean (Coc et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…In total 1446 microplastic in 20 specimens' digestive tract of Stichopus horrens were reported in Pulau Pangkor, Perak, Malaysia (Husin et al, 2021). Digestive tract of three different sea cucumber species (Holothuria atra, Holothuria scabra, Sticopus variegatus) was investigated by Idris et al (2022) and microplastic amounts of these species were found between 32-52 pieces/ind. in Bintan Island, Riau Archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…the study site. This is similar to [9] that microplastics are dominated by the fiber type followed by the fragment type. According to [18], the spread of microplastic fiber types can be affected due to fishing activities, such as degraded fishing rods and nets.…”
Section: Microplastic Types In Strombus Sp and Sedimentsupporting
confidence: 86%
“…According to [8], the size and colour of microplastics that resemble food will cause microplastics to be consumed by marine biota. Previous research conducted by [9] showed that microplastics have been found in the digestive tract of sea cucumber organisms that live in seagrass. Based on this, there is a need for research on the characteristics of microplastics in barking snails (Strombus sp.)…”
mentioning
confidence: 99%
“…Sea cucumbers' gastrointestinal tracts include three different kinds of microplastics: fibre, pieces, and balls. According to multiple earlier investigations, fibre and fragments were also discovered in the digestive tracts of sea cucumbers on Tidung Island and Bintan Island (Sayogo et al, 2020;Idris et al, 2022). Numerous other kinds of microplastics are discovered in the digestive tract of different species of sea cucumber.…”
Section: Resultsmentioning
confidence: 99%